Optimization of Crude Protease Production from Bacillus thuringiensis HSFI-12 and Thrombolytic Activity Its Enzyme Dialysate - Zafrida, Siska; Ethica, Stalis Norma; Ernanto, Aditya Rahman; Wijanarka, Wijanarka (Trends in Sciences, 2022)
Cardiovascular disease (CVD) is among the leading causes of death in the world caused by thrombosis. Thrombosis is the formation of excessive blood clots on the walls of blood vessels called thrombus. This could lead to fatal blockage of the heart muscle or brain. Thrombosis can be treated using enzyme-type drugs such as thrombolytic proteases. There have been many studies of bacteria producing thrombolytic enzymes isolated from fermented foodstuffs. However, commercial production of bacterial enzymes to fulfill the need of thrombolytic agents is still limited, causing high price of CVD therapy. Bacillus sp. HSFI-12 (Holothuria scabra Fermented Intestine-12) isolated from the fermented intestine of sea cucumber Holothuria scabra had been reported to have a competitive thrombolytic activity to the commercial Nattokinase. This study aimed to determine bacterial optimum incubation time based on enzyme activity after bacterium molecular identification was done. It also aimed to obtain the dialysate of bacterial crude protease and then determine the thrombolytic activity of the obtained dialysate. Thrombolytic activity was tested on 4 different types of blood (A, B, AB and O). Results of molecular identification showed that strain HSFI-12 shared similarity level of 99.80 %, with Bacillus thuringiensis. Activity of crude protease from the incubated cultures peaked at 48 h of incubation with activity of 191.5 U/mL The activity of concentrated protease after precipitation and dialysis process (dialysate) was 2-times higher by 355,7 U/mL. The percentage of lysis of blood clots produced by crude blood groups A, B, AB and O showed a range of values ​​of 66.423 - 67.656 % while those that produce dialysate are 77.564 - 78.861 %. As conclusion, the best (optimized) incubation time to produce crude enzyme from B. thuringiensis HSFI-12 with the highest activity was 48 h. The process of concentrating the crude thrombolytic protease of B. thuringiensis HSFI-12 increases both activity and thrombolytic ability of the bacterial enzyme. HIGHLIGHTS The most optimum incubation time for protease production from Bacillus thuringiensis is 48 h Partial purification on bacterial crude protease through resulted in 86 % increased activity Partial purification on bacterial crude protease resulted in 17 % increased blood clot lysis ability Clot lysis ability of both crude and dialysate proteases are higher than that of Nattokinase (NK) GRAPHICAL ABSTRACT